The Effect of Financial Disruption, Profitability and Audit Quality on Audit Report Lag (Empirical Study on Manufacturing Companies on the IDX for the 2018 – 2022 Period) - Raul Jordan Reevhandy Lau; Apollo Daito (International Journal of Economics, Management and Accounting, 2025)
This study examines the phenomenon of delays in the delivery of financial reports (audit report lag) which can cause negative reactions from investors and other users of financial reports. This delay is often seen as a bad signal and can indicate stock price fluctuations. Variables studied in this study include financial distress, profitability, and audit quality and their effects on audit report lag. This study uses objects in the form of manufacturing companies listed on Indonesia Stock Exchange (IDX) in period 2018-2022. The study population includes all manufacturing companies, and the sample was selected using a purposive sampling technique, which resulted in 50 companies as samples with a total of 250 observation data. The method used in this study is quantitative analysis with a statistical approach using multiple linear regression run on the SPSS version 25 program. Tests were conducted to determine the effect of financial distress, profitability, and audit quality on audit report lag. The results showed that financial distress has a positive effect on audit report lag, while profitability and audit quality have a negative effect on audit report lag.